Penguatan ecological citizenship berbasis Sungai sebagai upaya mewujudkan karakter peduli lingkungan di Kelurahan Kasang - Oktalia, Delvia; Anderson, Irzal; Melisa, Melisa (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The aim of this research is to identify barriers to achieving environmentally conscious behavior in Kasang Village, Jambi City, and how to improve river-based eco-citizenship to foster environmentally conscious character in the community. A descriptive approach was used in this qualitative research. Interviews, observations and documentation were the data collection methods used in this research, which involved two RT heads and ten residents as informants. The data analysis methods used include reduction, data display and drawing conclusions. The results of this research indicate that strengthening river-based ecological citizenship in Kasang Village, Jambi City, researchers carried out additional outreach regarding strengthening ecological citizenship regarding rivers, ethical and moral procedures for the community in dealing with the environment and overcoming environmental problems. The community is aware of the obligation to protect rivers by disposing of rubbish in temporary dumping sites and recycling rubbish for learning in schools and the obstacles in strengthening ecological citizenship. There are no special government programs for protecting the river environment. There are only environmental programs around the river basin